On the Definition of Circular Migration - Eganyan, Ruben (Journal of Sociology: Bulletin of Yerevan University, 2015)
In the article, on the basis of critical analysis of the existing definitions of the comparatively new scientific term “circular migration”, its essence, content and signs, the main, the most important sign is defined, by which this phenomenon is distinguished from other forms of temporary migration, and which became the main reason for emphasizing and examining it as a new, independent form of migration.
Keywords: temporary migration, circular migration, labor migration